2020
DOI: 10.1039/d0ra01869d
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous tuning of optical and electrical properties in a multifunctional LiNbO3 matrix upon doping with Eu3+ ions

Abstract: PL and dielectric studies have been carried out on LiNbO3 and Eu3+:LiNbO3 compounds with a special focus on simultaneous tuning of optical and electrical properties for their potential application in optical–electrical integration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…Lithium Niobate (LiNbO 3 ) is a widely recognized perovskite compound that displays ferroelectric properties and holds significant potential for use in optical and electro‐optical systems, thanks to its unique piezoelectric, electro‐optical, and photovoltaic, photoelastic, and nonlinear optical properties [1‐23]. Researchers have become interested in LiNbO 3 because of its extraordinary and unusual features, mostly determined by its structural composition and defect structure.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lithium Niobate (LiNbO 3 ) is a widely recognized perovskite compound that displays ferroelectric properties and holds significant potential for use in optical and electro‐optical systems, thanks to its unique piezoelectric, electro‐optical, and photovoltaic, photoelastic, and nonlinear optical properties [1‐23]. Researchers have become interested in LiNbO 3 because of its extraordinary and unusual features, mostly determined by its structural composition and defect structure.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have explored the impact of metal doping on the optical properties of LiNbO 3 . Pathak et al [20] investigated the effects of Eu3+$$ {\mathrm{Eu}}^{3+} $$ doping and found that it improved the optical properties of LiNbO 3 . Hui et al [21] studied the impact of Fe and Mg doping, while Bachiri et al [22] examined the influence of Ni doping.…”
Section: Introductionmentioning
confidence: 99%
“…In order to obtain such multifunctional materials, [22][23][24] great efforts have been made to explore the relationship between their inherent structure and potential properties. For example, Wu et al 25 reported chiral Zn-based organicinorganic hybrid RMPZnS 2 and SMP 2 ZnS 3 single crystals with a large polarization value of 9.5 μC cm −2 and luminescence characteristics.…”
mentioning
confidence: 99%